KOMPARASI PEMBANGUNAN POTENSI WISATA DI DESA PEMANGKAT DAN DESA TANJUNG KALIMANTAN BARAT - Yuyun; Rafikah Mukhlisah; Eriska Dewi Maniza; Annisa Rizqa Alamri; Mislajima; Deni (STABN Raden Wijaya Wonogiri, 2023)
This article aims to identify how development compares to tourism potential in Pemangkat Village and Tanjung Village. The difference is in the form of infrastructure and local government involvement in supporting the tourism potential of the two villages. This study uses descriptive qualitative research methods, namely by carrying out the process of collecting data through the process of observation, documentation and interviews. Informants in this study were five people selected based on snowball sampling. This study describes a tourist village in West Kalimantan, so this research explains the differences and comparisons of the two tourism villages. The results of this study indicate that the surrounding community is highly participating in advancing this tourism. This can be seen in the construction of facilities through government assistance, while Tanjung Village still requires assistance from the government and related stakeholders. Keywords: Community, Potential, Tourism.